(untitled) (Revista Internacional de Folkcomunicação, 2021)
The Economist. The present study aims to discuss a historical record of Brazil, based on a complimentary and even euphoric look, about it in the British newspaper The Economist during the second term of former President Lula. The vehicle is regarded by economists and financial market experts from around the world as the bible of world liberalism; with this "brand" The Economist goes from panic with the imminent victory of the former union leader in 2002 to enthusiasm for the former Head of State of Latin America’s greatest economic power house in less than a decade! This paper, with theoretical foundation surrounded by discourse analysis and important folkcommunicational aspects, makes a return to a recent historical past, however, extremely distant from the current Brazilian reality, in which the crisis permeates various sectors and the folk language, light, peaceful gave way to the discourse of "denialism" in the face of social demands of emergency order, as is the case of hunger , employment, public health. Finally, what was "marolinha" in the economy of the Lula Government, turning into praise and example for the whole planet, today seems a distant historical record. It is the aforementioned record that now presents itself, involving the speech as the central axis of the folk image of a former Brazilian president who brought praise and euphoria to his country. Brazil; Folkcommunication; Lula; The Economist.